Factors influencing intercultural doctor–patient communication: A realist review. Issue 4 (April 2015) - Paternotte, Emma; van Dulmen, Sandra; van der Lee, Nadine; Scherpbier, Albert J.J.A.; Scheele, Fedde
Highlights Intercultural communication is comparable with patient-centered communication. The context and mechanisms of intercultural communication influence outcome. Mechanisms for training are communication objectives, core and specific communication skills. Realist review uses an explanatory focus to learn the interplay of communication.